A multi‐scale approach reveals that NF‐κB cRel enforces a B‐cell decision to divide. Issue 2 (13th February 2015) - Shokhirev, Maxim N; Almaden, Jonathan; Davis‐Turak, Jeremy; Birnbaum, Harry A; Russell, Theresa M; Vargas, Jesse A D; Hoffmann, Alexander
Abstract: Understanding the functions of multi‐cellular organs in terms of the molecular networks within each cell is an important step in the quest to predict phenotype from genotype. B‐lymphocyte population dynamics, which are predictive of immune response and vaccine effectiveness, are determined by individual cells undergoing division or death seemingly stochastically. Based on tracking single‐cell time‐lapse trajectories of hundreds of B cells, single‐cell transcriptome, and immunofluorescence analyses, we constructed an agent‐based multi‐modular computational model to simulate lymphocyte population dynamics in terms of the molecular networks that control NF‐κB signaling, the cell cycle, and apoptosis. Combining modeling and experimentation, we found that NF‐κB cRel enforces the execution of a cellular decision between mutually exclusive fates by promoting survival in growing cells. But as cRel deficiency causes growing B cells to die at similar rates to non‐growing cells, our analysis reveals that the phenomenological decision model of wild‐type cells is rooted in a biased race of cell fates. We show that a multi‐scale modeling approach allows for the prediction of dynamic organ‐level physiology in terms of intra‐cellular molecular networks. Synopsis: A new multi‐scale model predicts B‐cell population dynamics in terms of intra‐cellular molecular networks. We predict and confirm that NF‐κB cRel enforces cellular fate decisions and characterize how molecular network noise determines robust cell population dynamics. We present a multi‐scale model that accounts for robust B‐cell population dynamics in terms of noisy molecular network dynamics in each cell. Live cell microscopy confirms that cells entering a growth phase constitute a fate decision toward division rather than death. Modeling and experimentation reveal that NF‐κB cRel is critical for enforcing the fate decision—its absence results in a 'fate race'. The multi‐scale model can predict how molecular perturbations and extrinsic noise effect cell population dynamics. Abstract : A new multi‐scale model predicts B‐cell population dynamics in terms intra‐cellular molecular networks. We predict and confirm that NF‐κB cRel enforces cellular fate decisions and characterize how molecular network noise determines robust cell population dynamics.